ANALISIS STRATEGI PENINGKATAN NILAI PERUSAHAAN PADA BANK DIGITAL DI INDONESIA - Mainatul Ilmi; Ahmad Sauqi; Putri Ulan Tansyiah (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to analyze the influence of bank soundness, bank size, and working capital management on firm value, with profitability as an intervening variable in digital banks in Indonesia. This research adopts a quantitative exploratory approach. The population consists of 15 digital banking companies. Using a purposive sampling technique, 5 digital banks were selected as the research sample. The analytical method employed is Structural Equation Modeling (SEM) with Path Analysis. The results indicate that bank soundness has a positive but non-significant effect on profitability and a negative non-significant effect on firm value. Bank size has a negative non-significant effect on profitability but a negative significant effect on firm value. Working Capital Management (WCM) shows a positive but non-significant effect on profitability and a positive significant effect on firm value. Profitability has a negative non-significant effect on firm value. Furthermore, the mediation test results reveal that profitability is unable to mediate the influence of bank soundness, bank size, or WCM on firm value. Overall, this research demonstrates that for digital banks in Indonesia, corporate value is more heavily influenced by the efficiency of working capital management and company scale rather than bank soundness and profitability. Investors tend to prioritize operational stability, financial management efficiency, and long-term growth prospects over short-term financial performance. These findings imply that digital bank management needs to focus their strategies more on improving operational efficiency and optimizing working capital management to create sustainable firm value.